Multi-Objective Topology Optimization for Curved Arm of Multifunctional Billet Tong Based on Characterization of Working Conditions - Zhaohua Wang; Dezhuang Song; Fenghe Wu; Jialiang Liu (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
A windlass driven heavy duty multifunctional billet tong was designed for large-scale forging and casting to reduce the number of auxiliary material handling devices in manufacturing workshops. To improve its mechanical performance and safety, a novel multi-objective topology optimization method for its curved arm is proposed in this paper. Firstly, the influence of different open angles and working frequencies for the curved arm was simplified to a multi-objective optimization problem. A comprehensive evaluation function was constructed using the compromise programming method, and a mathematical model of multi-objective topology optimization was established. Meanwhile, a radar chart was employed to portray the comparative measures of working conditions, the weight coefficient for each working condition was determined based on the corresponding enclosed areas, combining the stress indices, the displacement indices and the frequency indices of all working conditions. The optimization results showed that the stiffness and strength of the curved arm can be improved while its weight can be reduced by 10.77%, which shows that it is feasible and promising to achieve a lightweight design of the curved arm of a billet tong. The proposed method can be extended to other equipment with complex working conditions.